Zespół SAPHO jako wyzwanie terapeutyczne - opis przypadku - Grażyna Chodorowska; Ewa Wielosz; Maria Juszkiewicz-Borowiec; Agnieszka Gerkowicz; Anna Michalak-Stoma (Termedia Publishing House, 2011)
acne, pustulosis, hyperostosis and osteitis. The aetiology of this syndromeis not fully recognized.Objective. To present a case of a 17-year-old boy with SAPHO syndrome.Case report. A 17-year-old boy was admitted to the DermatologyDepartment due to severe acne lesions, plantar pustulosis and psoriaticplaques. Skin lesions were accompanied by severe pain of the leftknee. The patient reported pain in the anterior chest wall appearingoccasionally. On physical examination, limitation of mobility of the thoracic and lumbar vertebral column was noticed. The skin biopsyconfirmed the diagnosis of plantar pustular psoriasis. A vertebral columnX-ray, chest X-ray, bone scintigraphy and several laboratory testswere performed. Based on clinical, laboratory and radiological findingsthe SAPHO syndrome was diagnosed. The patient was treated withantibiotics, sulfasalazine, etanercept and methotrexate.Conclusions. The SAPHO syndrome combines bone and join manifestationsassociated with skin lesions. Due to the unknown aetiology ofthis syndrome the treatment remains empirical, and therapy should beadapted to the individual patient.